Restoration of Degraded Pastureland Ecosystem in Semi-arid Rajasthan: A Study of Two Villages - Ray, Sunil; Upadhyay, Alka (Annals of Arid Zone, 2016)
The paper shows how degraded pastureland ecosystem was restored through adoption of silvopastoral mode of grassland development in Chhota Saradhana and Singhariya villages. It also shows how improved status of the ecosystem in terms of 110ml diversity and soil characteristics was maintained despite persistent drought that the region experienced for three years (2000-2003). It underscores the role of the community institution at the village level for sustainable management of the lands under new institutional practices. Key words: Floral diversity, institutional renovation drought, soil characteristics, conservation.